Sex differences in a mouse model of multiple sclerosis: neuropathic pain behavior in females but not males and protection from neurological deficits during proestrus - Rahn, Elizabeth J (BioMed Central, 2014)
BACKGROUND: Multiple sclerosis (MS), a demyelinating disease of the central nervous system, is one of the most prevalent neurological disorders in the industrialized world. This disease afflicts more than two million people worldwide, over two thirds of which are women. MS is typically diagnosed between the ages of 20–40 and can produce debilitating neurological impairments including muscle spasticity, muscle paralysis, and chronic pain. Despite the large sex disparity in MS prevalence, clinical and basic research investigations of how sex and estrous cycle impact development, duration, and severity of neurological impairments and pain symptoms are limited. To help address these questions, we evaluated behavioral signs of sensory and motor functions in one of the most widely characterized animal models of MS, the experimental autoimmune encephalomyelitis (EAE) model. METHODS: C57BL/6 male and female mice received flank injection of complete Freund’s adjuvant (CFA) or CFA plus myelin oligodendrocyte glycoprotein 35-55 (MOG(35-55)) to induce EAE. Experiment 1 evaluated sex differences of EAE-induced neurological motor deficits and neuropathic pain-like behavior over 3 weeks, while experiment 2 evaluated the effect of estrous phase in female mice on the same behavioral measures for 3 months. EAE-induced neurological motor deficits including gait analysis and forelimb grip strength were assessed. Neuropathic pain-like behaviors evaluated included sensitivity to mechanical, cold, and heat stimulations. Estrous cycle was determined daily via vaginal lavage. RESULTS: MOG(35-55)-induced EAE produced neurological impairments (i.e., motor dysfunction) including mild paralysis and decreases in grip strength in both females and males. MOG(35-55) produced behavioral signs of neuropathic pain—mechanical and cold hypersensitivity—in females, but not males. MOG(35-55) did not change cutaneous heat sensitivity in either sex. Administration of CFA or CFA + MOG(35-55) prolonged the time spent in diestrus for 2 weeks, after which normal cycling returned. MOG(35-55) produced fewer neurological motor deficits when mice were in proestrus relative to non-proestrus phases. CONCLUSIONS: We conclude that female mice are superior to males for the study of neuropathic pain-like behaviors associated with MOG(35-55)-induced EAE. Further, proestrus may be protective against EAE-induced neurological deficits, thus necessitating further investigation into the impact that estrous cycle exerts on MS symptoms.